Microscopic origin of the enhanced piezoelectric thermal stability in acceptor doped lead-free Ba(Ti0.8Zr0.2)O3-50(Ba0.7Ca0.3)TiO3 ceramic. Issue 4 (15th February 2022) - Yin, Mengye; Fang, Minxia; Zhang, Lixue; Zhou, Chao; Xiao, Andong; Ji, Yuanchao; Ma, Tianyu; Ren, Xiaobing
Abstract: Acceptor doping is effective in enhancing thermal stability in piezoceramics, while the reason underlying is still unclear and awaits explanation. In this work, through doping acceptor Mn in lead-free Ba(Ti0.8 Zr0.2 )O3 -50(Ba0.7 Ca0.3 )TiO3 ceramic, our results show that doping Mn achieves higher depolarization temperature, even higher than Curie temperature ( T C ) and simultaneously a better piezoelectric thermal stability. Through microscopic and macroscopic analysis, the enhancement can be explained by the clamping effect induced by acceptor doping, which is carefully demonstrated by symmetry-conforming short-range ordering tendency theory. Thus, this work reveals the mechanism for enhanced depolarization temperature and piezoelectric thermal stability due to acceptor doping and will help developing new thermal stable lead-free piezoceramics applicable in a wider temperature range.